Relationship between the fungiform papillae number and dental caries in primary teeth: a cross-sectional study - MENTEŞ, ALİ RECAİ (SPRINGER HEIDELBERG, 2021)
Objectives Fungiform papillae (FP) contain numerous taste buds. A genetic susceptibility between tasting via FP and caries risk has been suggested. This study aimed to investigate the relationship between FP number and dental caries and to determine whether FP number may be considered as a test for caries risk. Materials and methods The study included 157 children who attended the pediatric dentistry department at a public university. Questionnaires, including the children's medical health, oral health knowledge, fluoride exposure, and taste preferences, were filled in by their parents. The FP number on the dorsal surface of the tongue was counted according to the Denver Papilla Protocol. Caries was recorded using deft/DMFT indices. Statistical analyses were performed using SPSS. Results The FP number decreased significantly according to age (r = -0.441, p = 0.001), and the mean of the girls' FP number was significantly higher than the boys' (p = 0.022). A greater number of FP was associated with increased deft score (p = 0.02, odds ratio [OR] = 1.164). Conclusion The caries risk increased in children who had more FP (FP > 30); therefore, FP number could be evaluated in terms of caries risk. FP number could be evaluated as a risk factor for determining dental caries since the risk of caries increased after a FP cut-off point of 29 was achieved.
Keywords: Caries; Caries risk; Fungiform papillae; Taste preference; Tongue; DENSITY